The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1080/13676261.2020.1849584
|View full text |Cite
|
Sign up to set email alerts
|

‘Because I am me': school bullying and the presentation of self in everyday school life

Abstract: In this study, we draw on Erving Goffman's work on the presentation of self to explore responses by 12-15-year-old (i.e. 6th-9th grade) school students to an open-ended survey question about why they think they were bullied. In doing so, we contribute to a relatively unexplored aspect of school bullying research by focussing on how those students who are subjected to bullying understand their own bullying experiences. We focus in particular on explanations that focus on themselves as individuals. Utilising the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…First, as predicted in the first hypothesis, it was observed that adolescents with high levels of guilt presented greater school victimization-physical, overt, and relational-, which was in line with previous studies (Chen and Chen, 2019;Tholander et al, 2020). These findings are, in our view, highly relevant as various studies have pointed out that adolescents showing irrational guilt tend toward internal attribution of their victimization (Wei-Ru and Li-Ming, 2019;Forsberg and Horton, 2020), which may inhibit the search for external support (Harsey et al, 2017), and are therefore more likely to face prolonged victimization (Schacter and Juvonen, 2017). We consider these results interesting because they contribute to deepening our understanding of victim coping strategies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, as predicted in the first hypothesis, it was observed that adolescents with high levels of guilt presented greater school victimization-physical, overt, and relational-, which was in line with previous studies (Chen and Chen, 2019;Tholander et al, 2020). These findings are, in our view, highly relevant as various studies have pointed out that adolescents showing irrational guilt tend toward internal attribution of their victimization (Wei-Ru and Li-Ming, 2019;Forsberg and Horton, 2020), which may inhibit the search for external support (Harsey et al, 2017), and are therefore more likely to face prolonged victimization (Schacter and Juvonen, 2017). We consider these results interesting because they contribute to deepening our understanding of victim coping strategies.…”
Section: Discussionsupporting
confidence: 89%
“…According to Graham and Juvonen (1998), following an episode of victimization, two internal attributions of blame may emerge: characterological and behavioral. Characterological guilt refers to the perception that negative experiences are attributed to internal, stable, and uncontrollable causes, which may inhibit the victim from seeking external help and support (Forsberg and Horton, 2020;Tholander et al, 2020), whereas behavioral guilt relates to specific controllable actions. For instance, an adolescent may attribute being victimized by a peer to being an unpleasant person (characterological guilt) or to not being kind enough that day (behavioral guilt).…”
Section: Feelings Of Guilt and School Victimizationmentioning
confidence: 99%
“…In relation to the reason why the victims considered they were bullied, in line with Forsberg and Horton (2020) , attributions of an internal nature, of self-blame and linked to issues related to skills, character, physical characteristics and with presenting some type of disability were observed. This internal attribution of the situation (self-blame) may lead to a higher probability of continuing to receive bullying and the appearance of depressive symptoms, making an intervention linked to attributional change necessary ( Schacter et al, 2015 ).…”
Section: Discussionmentioning
confidence: 82%
“…Despite a lack of sport skills is a relevant trigger when it comes to suffering from bullying, some of the victims claimed to have been bullied for showing superior sport skills compared to the rest of their teammates. Following the Social Comparison Theory by Festinger (1954) and, in the same way it occurs in the educational environment, especially among boys ( Bergold et al, 2020 ), some athletes who become aggressors may feel threatened and jealous of those with better sport skills ( Forsberg and Horton, 2020 ). Victims also explained that personality traits such as shyness were also a reason to become a victim, since this leads them to have less ability to defend their own physical and psychological integrity ( Hernández and Saravia, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ireland et al (2020) reveal the preconditions for the intervention of guardianship authorities during cyberbullying in the process of interpreting incidents, collective and automated psycho-correction regarding the relative popularity of hooligans. Forsberg and Horton (2020) present a video report on "Because I am Me" about school bullying and self-presentation in everyday school life. Horton (2019) thoroughly describes school bullying and the limited nature of outcasts in society.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%